A study of adaptive reuse shophouse building / Muhammad Hilman Mohd Omar and Aida Affina Abdul Ghani - Mohd Omar, Muhammad Hilman; Abdul Ghani, Aida Affina (2019)
Adaptive Reuse is the process of reusing an old building for an entirely new different purpose other than that which the building was made for originally. Adaptive reuse is very important in Malaysia as it helps to save heritage buildings from being demolished to satisfy modern needs. The problem was most of them were not able to be maintained due to lack of funds and there were several shophouses scorched in fire and the owners did not do any repair work on the building. The literature review refers to the to the journals, books, articles, newspaper. A mixed method is used in conducting research involving the collection and analysis of quantitative methods and qualitative methods. The data collection was based on the adaptive reuse done at the shop building in Oldtown, Ipoh, Perak. All data collected during the distribution of questionnaires and condition survey observation were analyzed using SPSS and Microsoft Words. The findings are carried out after analyzing the data of research and suggestions for recommendations are proposed after the research findings have been identified.